Integration of STEAM and Digital Teaching Materials: A Prototype of a Science Learning Model for Elementary School Students - Amran, Muhammad; Arismunandar, Arismunandar (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This research aims to develop a STEAM (Science, Technology, Engineering, Art, and Mathematics) learning model based on digital science teaching materials to improve students' creativity. The research approach used is Research and Development (R&D) with a development model that includes needs analysis, design, development, validation, implementation, and evaluation. The research subjects were students at the secondary education level who were involved in limited trials and extensive trials. The results showed that the STEAM-based digital teaching materials developed were in accordance with the principles of innovative learning. The implementation of the model in the classroom shows an increase in learner creativity, which is reflected in their increased ability to think critically, solve problems, and generate new ideas in science learning. Thus, the development of a STEAM learning model based on digital teaching materials can be an alternative learning strategy in improving students' creativity. Recommendations from this study are the integration of learning models into the school curriculum as well as training for teachers in the application of this model for more optimal results.